Mapeamento estratégico dos biomateriais utilizados em implantes - Santos, Gustavo Roberto dos [UNESP] (2019)
With the ever-faster advances in technology used on healthcare area and the development of new materials, products and surgical techniques, it has become possible for professionals in this field to perform procedures more efficiently, as well, for patients, a faster recovering and improvement on quality of life. The objective of this work is to develop a strategic mapping of biomaterials used in implants on health area, seeking an understanding of the market and Research & Development area. Researches into scientific data bases Scopus and Web of Science were performed, as well economic searching into Abimo and Comex Stat databases using the structured process based on the Systematic Search Flow (SSF) method. The search strategy includes collecting data from 2012 to 2018 related to the following application areas: Cardiology, Dental, Orthopedics and Ophthalmology; also, with the material groups: Metals, Polymers, Ceramics and Naturals. Among the two databases used, Scopus has presented the largest number of published articles, about 58.49% against 51.51% of Web of Science. Regarding to the progress of scientific production in biomaterials area, we can say that in the material science, Metals are the most interest in development of research, seeking new techniques and methods to improve people's quality of life. There were 20,167 publications made in the period, where 50.56% are from the Metals group. In Brazil, there is a prevalence of small and medium companies: almost 74% of the total, with revenues within R$ 240 k to R$ 2.4 M for small companies, and within R$ 2.4 M to R$ 6 M for medium companies. The biomaterials market is increasingly becoming a strategic area in terms of the great economic potential in all sectors and areas in Brazil, Latin America and the world.